2012
DOI: 10.1302/0301-620x.94b12.29958
|View full text |Cite
|
Sign up to set email alerts
|

Development of the osseous and cartilaginous acetabular index in normal children and those with developmental dysplasia of the hip

Abstract: The purpose of this study was to investigate the development of the osseous acetabular index (OAI) and cartilaginous acetabular index (CAI) using MRI. The OAI and CAI were measured on the coronal MR images of the hip in 81 children with developmental dysplasia of the hip (DDH), with a mean age of 19.6 months (3 to 70), and 241 normal control children with a mean age of 5.1 years (1 month to 12.5 years). Additionally the developmental patterns of the OAI and CAI in normal children were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 30 publications
10
40
0
3
Order By: Relevance
“…Several studies have reported that DDH is associated with increased acetabular cartilage thickness and delayed endochondral ossification of the roof of the acetabulum 7,12,13 . In the present study, MRI analysis demonstrated that acetabular roof cartilage in the rabbit DDH model was significantly thicker than that of the contralateral control side.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Several studies have reported that DDH is associated with increased acetabular cartilage thickness and delayed endochondral ossification of the roof of the acetabulum 7,12,13 . In the present study, MRI analysis demonstrated that acetabular roof cartilage in the rabbit DDH model was significantly thicker than that of the contralateral control side.…”
Section: Discussionsupporting
confidence: 57%
“…During childhood, the roof of the acetabulum consists of both cartilaginous and osseous parts. We have previously evaluated both the cartilaginous and osseous acetabular components in childhood DDH cases to validate their importance in the pathogenesis of the disease 7 . The results of that study indicated that in certain pediatric cases of DDH, despite the prominent acetabular dysplasia observed on radiographs, sufficient cartilaginous acetabular cover could be detected by magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the cost and possible requirement of additional sedatives, the advantages of MR imaging are considerable in DDH assessment, including the absence of radiation, possibility of imaging in multiple planes, and higher resolution and contrast between bony and cartilaginous components. [12] The high accuracy of MRI in demonstrating the details of DDH has been described in previous literature by comparing with anatomical preparations in cadavers. [13,14] More recently, MRI is being used in the diagnosis of the anatomical obstructions to reduction, such as brofatty pulvinar tissue, joint effusion, thickened ligamentum teres, inversed and thickened labrum, and iliopsoas muscle atrophy.…”
Section: Discussionmentioning
confidence: 92%
“…Recent orthopaedic articles have described the utility of both bony and cartilaginous acetabular indexes on MRI in the evaluation of DDH. 32,33 After successful reduction, the femoral head should be located concentrically in the acetabulum. 34…”
Section: Congenital/developmentalmentioning
confidence: 99%